A Resilience Intervention to Increase Academic Persistence Among Undocumented Students in Higher Education. (October 2020) - Kwon, Paul; Pattinson, Marcela Carillo; Faust, Emily; Hobaica, Steven; Tse, Joseph; Sainz, Rebeca; Castañeda, Cesar; Graham, Brittany S.; Keiser, Gregory H.
We designed a resilience intervention in the form of a self-help workbook. It was made to address the challenges of being an undocumented student. The workbook includes modules on increasing social support, hope for the future, and emotional openness. In an initial feasibility study, participants reported that the workbook contains valuable information. A second feasibility study that incorporated eight weekly group meetings led to significantly higher ratings regarding the utility of the intervention.